Application of Bismuth‐Impregnated Mesoporous Silica to the Photochemical Oxidation of Methylene Blue: An Example of Nanoparticle Autocatalysis. Issue 4 (18th February 2013) - Ward, Antony J.; Weber, Cameron C.; Masters, Anthony F.; Maschmeyer, Thomas
Abstract A range of Bi‐TUD‐1 silicas were used in conjunction with H2O2 to mediate the photochemical oxidation of methylene blue (MB). The rate of MB degradation increased sequentially with decreasing metal loading, and it was determined experimentally that singlet oxygen was responsible for the oxidation process observed. Kinetic studies of the system revealed that putative reactive BiV‐containing surface sites are generated autocatalytically by irradiation of the Bi‐TUD‐1 in the presence of peroxide. The formation of these active sites is favored by lower Bi concentrations resulting in the formation of smaller Bi species in the silica framework. Total organic carbon analysis of the reaction mixtures showed that MB was being converted to CO2 after the decolorization process had occurred.